INVENTARISASI GULMA PADA TANAMAN JAGUNG (Zea mays L.) DATARAN TINGGI DI DESA PALELON DAN DATARAN RENDAH DI KELURAHAN KIMA ATAS - Keren Selia Amy Assa; Pemmy Tumewu; Grace Tulungen (COCOS, 2017)
SUMMARY This research aims to inventory the weeds associated  in corn field in the highland and lowland.  This research was conducted  in two places on  corn field in the highlands at Palelon Village Distric Modoinding Regency South  Minahasa with altitude 975 metres AMSL and on corn field in at the lowlands Village Kima Atas Distric Mapanget Manado City with altitude 73 metres AMSL. Research conducted in  may to june 2016. Research used  survey method and data collection  by using the square method with make distribution of sample plots. Weeds data analysis using the formula  SDR (Summed Dominance Ratio). Observed variable that is  weed species,  number of weed, and dominance weed. The result obtained 10 weed species in the highland and 17 weed species in lowland area. The inventory results weed obtained three species of weed  highlands has SDR  value higher compared than other species  that is Paspallum conjugatum with the SDR value of each strata   (35,22 %, 38,77%,  37,66), Ageratum conyzoides with SDR value (28,99%, 30,15%, 25,89% ), Drymaria cordata with the SDR (8,8 %, 18,24%, 5,70%). While the three species of weeds lowland has SDR value higher compared  than other  species  that is Cynodon dactilon with SDR every stratum is (29,70 %, 50,24 %), Sida rhombifolia  with the SDR (12,12%,  23,69 %,  28,18 %), Calopogonium mucunoides with the SDR (2,95%, 14,29%, 29,09% ).   From the research  suggested  weed control of asteraceae family can be done mechanically, chemical by using herbicides systemic.  Poaceae can be done by mechanical or chemically. Key words : Weeds inventory, weed, weed corn field.